2015
DOI: 10.1007/s10840-015-9974-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute conversion of persistent atrial fibrillation during dofetilide loading does not predict long-term atrial fibrillation-free survival

Abstract: Acute pharmacologic conversion of persistent AF/AFl to sinus rhythm frequently occurs during dofetilide loading. Nevertheless, acute pharmacologic conversion does not predict long-term arrhythmia control, which was moderate at best.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
4
6
0
Order By: Relevance
“…The study confirmed previous observations that acute dofetilide administration has a high rate of pharmacologic conversion, in about half of patients, during initiation that would spare the need for deep sedation and electrical cardioversion. The present study cohort reflects contemporary usage of dofetilide that is mainly in healthier patients than initially studied, i.e., less heart failure and LV dysfunction.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The study confirmed previous observations that acute dofetilide administration has a high rate of pharmacologic conversion, in about half of patients, during initiation that would spare the need for deep sedation and electrical cardioversion. The present study cohort reflects contemporary usage of dofetilide that is mainly in healthier patients than initially studied, i.e., less heart failure and LV dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…Dofetilide was well‐tolerated and had infrequent safety events. Specifically, TdP ventricular tachycardia occurred in 1.0% of treated patients, in keeping with prior experience . The vast majority, nearly 90%, of exposed patients completed the six‐dose loading phase.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations